Role of transcription factors and chromatin modifiers in driving lineage reprogramming in treatment-induced neuroendocrine prostate cancer - Sreekumar, Amritha; Saini, Sharanjot (Frontiers in Cell and Developmental Biology, 2023)
Therapy-induced neuroendocrine prostate cancer (NEPC) is a highly lethal variant of prostate cancer that is increasing in incidence with the increased use of next generation of androgen receptor (AR) pathway inhibitors. It arises via a reversible trans-differentiation process, referred to as neuroendocrine differentiation (NED), wherein prostate cancer cells show decreased expression of AR and increased expression of neuroendocrine (NE) lineage markers including enolase 2 (ENO2), chromogranin A (CHGA) and synaptophysin (SYP). NEPC is associated with poor survival rates as these tumors are aggressive and often metastasize to soft tissues such as liver, lung and central nervous system despite low serum PSA levels relative to disease burden. It has been recognized that therapy- induced NED involves a series of genetic and epigenetic alterations that act in a highly concerted manner in orchestrating lineage switching. In the recent years, we have seen a spurt in research in this area that has implicated a host of transcription factors and epigenetic modifiers that play a role in driving this lineage switching. In this article, we review the role of important transcription factors and chromatin modifiers that are instrumental in lineage reprogramming of prostate adenocarcinomas to NEPC under the selective pressure of various AR-targeted therapies. With an increased understanding of the temporal and spatial interplay of transcription factors and chromatin modifiers and their associated gene expression programs in NEPC, better therapeutic strategies are being tested for targeting NEPC effectively.